Etats-Unis : sculptures du XXe siècle. - Goldscheider, Cécile; d'Harnoncourt, René (Paris : Musée Rodin, 1965)
Baskin, Leonard ; Bontecou, Lee ; Bourgeois, Louise ; Chamberlain, John ; Cornell, Joseph ; Ferber, Herbert ; Flannagan, John B. ; Hadzi, Dimitri ; Hague, Raoul ; Kiesler, Frédéric ; Lachaise, Gaston ; Lassaw, Ibram ; Lipton, Seymour ; Mallary, Robert ; Marisol, Escobar ; Nadelman, Elie ; Nakian, Reuben ; Nevelson, Louise ; Newman, Barnett ; Noguchi, Isamu ; Oldenburg, Claes ; Rickey, George ; de Rivera, Jose ; Rosati, James ; Segal, George ; Smith, David ; Spaventa, George ; Stankiewicz, Richard ; Suvero, Mark di ; Zogbaum, Wilfrid ; Zorach, William ; Calder, Alexander ; Callery, Mary ; Falkenstein, Claire ; Hayes, David V. ; Lee, Caroline ; Stackpole, Ralph
biografie
Etats-Unis : sculptures du XXe siècle, Musée Rodin, Paris, 1965
Frans
boek
Keywords: Amerika